A rare variation of ERCC8 gene cause Cockayne syndrome in a Chinese family - Ding, Fengjuan; Hou, Fei; Zhao, Bowen; Jin, Hua (Frontiers in Genetics, 2025)
BackgroundCockayne syndrome (CS) is a multisystem degenerative disorder in which dysplasia and microcephaly represent the primary criteria for diagnosis. we present the cases of two patients who exhibited distinctive facial features and a range of other clinical manifestations, including growth failure, developmental delay, microcephaly, dental anomalies, and unstable gait.MethodsClinical information pertaining to the patient’s family was collated and the Pedigree chart was drawn. Two milliliters of peripheral blood were drawn from each of the two patients (III1and III3) and their parents, The causative genes were identified by Medical exome sequencing. Furthermore, the pregnant women underwent amniotic fluid prenatal diagnosis at mid-pregnancy (III5).ResultsMedical exome sequencing revealed that both patients had a homozygous deletion of Exon4 in the ERCC8 gene and that both parents were carriers. Prenatal diagnosis by amniotic fluid confirmed that the fetus (III5) did not carry the variant.ConclusionThis clarified the diagnosis at the genetic level, deepened our understanding of the disease, and facilitated the ability to provide accurate genetic counseling and prenatal diagnosis, with the goal of reducing the number of new affected individuals in the family.